The product manager's desk reference - Haines, Steven (McGraw-Hill Education, 2014)
Introducing a brand-new Product Management Life Cycle (PMLC) model, this fully revised second edition provides the knowledge, tools, and insight you need to establish yourself as a cutting-edge product manager who contributes measurably to your company's success. Steven Haines clearly illustrates the entire product life cycle, from beginning to end. It is packed with an array of best practices and helpful hints that are critical to the efficient management of products. The book explains how to: choose and justify which products to build; plan for their profitable creation and deployment; develop and launch them; manage them once they enter the market; gracefully retire them and replace them with new products; and efficiently allocate investments across all of the products in an organization. --